Functionalized graphene nanocomposites and their derivatives : synthesis, processing and applications - Jawaid, Mohammad; Bouhfid, Rachid; Qaiss, Abou el Kacem (Elsevier Ltd. : Elsevier, 2019)
Functionalized Graphene Nanocomposites and Their Derivatives: Synthesis, Processing and Applications explains how the functionalization technique is used to create graphene nanocomposites, also exploring its current uses in industrial applications. Graphene-based nanocomposites are one of the major advancements in polymer-based materials, thus the synthesis, nanoscale dimensions, high aspect ratio, mechanical, electrical and thermal properties of graphene and its derivative have all been major areas of research in the last decade. This important reference covers these updates and is a critical book for those working in the fields of materials processing and characterization.